Uterine spiral artery muscle dedifferentiation. Issue 8 (26th July 2019) - Robson, A; Lash, G E; Innes, B A; Zhang, J Y; Robson, S C; Bulmer, J N
Abstract: STUDY QUESTION: Is vascular smooth muscle cell (VSMC) dedifferentiation a feature of uterine spiral artery (SpA) remodelling in early human pregnancy? SUMMARY ANSWER: Remodelling of human uterine SpAs is associated with dedifferentiation of VSMCs and can be induced in vitro by uterine natural killer (uNK) cells and extravillous trophoblast cells (EVTs). WHAT IS KNOWN ALREADY: Uterine SpAs undergo profound morphological changes in normal pregnancy with replacement of the musculoelastic arterial wall structure by fibrinoid containing EVTs. The fate of VSMCs in SpA remodelling is unknown; in guinea pig uterine artery VSMCs dedifferentiate, remain in the vessel wall and differentiate after parturition to restore the arterial wall. There is increasing evidence that uNK cells play a role in SpA remodelling. We hypothesized that SpA remodelling in human pregnancy is associated with VSMC dedifferentiation, initiated by uNK cell-derived growth factors. STUDY DESIGN, SIZE, DURATION: Formalin fixed, paraffin embedded placental bed biopsies were immunostained for angiogenic growth factor (AGF) receptors and markers of VSMC differentiation. An in vitro model of SpA remodelling using chorionic plate arteries (CPAs) was used to test the effect of different cell types and AGFs on VSMC differentiation. PARTICIPANTS/MATERIALS, SETTING, METHODS: Placental bed biopsies were immunostained for vascular endothelial growth factor receptors 1-3 (VEGF-R1, VEGF-R2, VEGF-R3), transforming growth factor beta 1 receptors I and II (TGF-βRI, TGF-βRII), interferon gamma receptors 1 and 2 (IFN-γR1, IFN-γR2), Tie2, α-smooth muscle actin (α-SMA), H-caldesmon (H-Cal), myosin heavy chain (MyHC), osteopontin and smoothelin. Staining intensity was assessed using a modified quickscore. Expression by VSMCs of the AGF receptors was confirmed by laser capture microdissection and real-time RT-PCR of non-remodelled SpAs, after laser removal of the endothelium. As an in vitro model, VSMC differentiation was assessed in CPAs by immunohistochemistry after culture in uNK cell-conditioned medium (CM), EVT-CM, uNK cell/EVT co-culture CM, Ang-1, Ang-2, IFN-γ, VEGF-A and VEGF-C, and after blocking of both Ang-1 and Ang-2 in uNK-CM. MAIN RESULTS AND THE ROLE OF CHANCE: SpA VSMC expression of Tie-2 ( P = 0.0007), VEGF-R2 ( P = 0.005) and osteopontin ( P = 0.0001) increased in partially remodelled SpAs compared with non-remodelled SpAs, while expression of contractile VSMC markers was reduced (α-SMA P < 0.0001, H-Cal P = 0.03, MyHC P = 0.03, smoothelin P = 0.0001). In the in vitro CPA model, supernatants from purified uNK cell (H-Cal P < 0.0001, MyHC P = 0.03, α-SMA P = 0.02, osteopontin P = 0.03), EVT (H-Cal P = 0.0006, MyHC P = 0.02, osteopontin P = 0.01) and uNK cell/EVT co-cultures (H-Cal P = 0.001, MyHC P = 0.05, osteopontin P = 0.02) at 12–14 weeks, but not 8–10 weeks, gestational age induced reduced expression of contractile VSMC markers and increased osteopontin expression. Addition of exogenous (10 ng/ml) Ang-1 ( P = 0.006) or Ang-2 ( P = 0.009) also reduced H-Cal expression in the CPA model. Inhibition of Ang-1 ( P = 0.0004) or Ang-2 ( P = 0.004) in uNK cell supernatants blocked the ability of uNK cell supernatants to reduce H-Cal expression. LIMITATIONS, REASONS FOR CAUTION: This is an in vitro study and the role of uNK cells, Ang-1 and Ang-2 in SpA remodelling in vivo has not yet been shown. WIDER IMPLICATIONS OF THE FINDINGS: VSMC dedifferentiation is a feature of early SpA remodelling and uNK cells and EVT play key roles in this process by secretion of Ang-1 and Ang-2. This is one of the first studies to suggest a direct role for Ang-1 and Ang-2 in VSMC biology. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a grant from British Biotechnology and Biosciences Research Council (BB/E016790/1). The authors have no competing interests to declare.